Heat treatment induces chemical changes and silica sol penetration in wood for properties improvement: hydrophobicity, thermal stability, and surface hardness. (1st March 2022) - Jiang, Jun; Li, Huixian; Pang, Jinhui; Mei, Changtong
Abstract: Thermal modification could act as pretreatment for promoting silica sol impregnation in wood. It could create extra available channels and spaces for silica transportation and deposition owing to the presence of micro-cracks and enlarged pore size. The significant improvements on anti-hygroscopicity, hydrophobicity, and dimensional stability of treated wood were attributed to the degradation of cell wall polymer (hemicellulose, cellulose, and lignin) and filling effect of silica in wood. The synergistic effect contained the reduction on –OH concentration owing to thermal degradation, and consumption of –OH groups via the interaction (Si–O–Si cross linked networks and Si–O–C covalent bonds) between silica and wood matrix. Furthermore, the degradation of cell wall polymers resulted in the increase of crystallinity in wood. However, the crystallinity turned to decrease due to the amorphous silica impregnation. The silica impregnation could compensate the mass loss caused by thermal degradation, leading to various weight percentage gains (WPGs) that depended on treatment temperature. Moreover, owing to the coverage and penetration of mineral silica in wood, acting as a thermal barrier, the thermal stability and surface hardness of treated wood improved prominently.